Interactive Mobile Home Tasks vs. Individual Home Tasks in University Foreign Language Education at the Upper-Intermediate Level - Elena Borzova; Maria Shemanaeva (MDPI AG, 2022)
Homework, being an indispensable part of learning, needs special planning and modification in line with the latest educational development. In this view, we assume that mobile devices can provide ample opportunities for students to interact and collaborate with their group-mates to enhance learning outcomes in university foreign language education. Interactive mobile homework assignments combined with individual ones can noticeably improve these outcomes from different perspectives. They engage students in communicative foreign language usage, encouraging both receptive and productive speech acts, student-to-student cooperation in learning through communication, peer-teaching, and pooling resources which promote the amplification of the learning environment through content and language sharing. On the other hand, interactive mobile homework assignments also have certain risks that may decrease the quality of learning, such as possible error exchange, a superficial approach, a switch to use of native language, and chatting, etc. Nevertheless, interactive mobile homework assignments keep students on the task for a longer period of time because they require each student's pre-task preparation, longer oral exchanges during the "while phase" and post-task individual summary, therefore providing more practice. The study described in the article highlights the characteristics of the interactive mobile homework tasks, suggests a list of homework task types, both individual and interactive, and compares the results of their practical application in university foreign language education. The authors attempt to identify a trend in their contribution to the learning outcomes achieved by the students while completing their homework, either interactively or individually.